Lights, camera...English!! : material design for an english teaching module based on film (2014)
This research project used film to develop an English teaching material that focuses on fostering the students speaking skill for the Low Advanced level in the BA in Modern Languages major at the Javeriana University. Film can be a valuable tool in the language teaching classroom, as a motivator, as authentic material, as a promoter of critical thinking, as a new field in education and as a language teaching tool. However, there is still a lot of potential in film left to explore. This project focuses on a specific aspect of that potential: its capacity to foster the speaking skill. Its main objective was to determine how a material based on film can foster this skill in a communicative way, in the context of the Low Advanced English class in the Javeriana University.